KAJIAN ETNOBOTANI MASYARAKAT DAYAK DI DESA TAU LUMBIS, KABUPATEN NUNUKAN, PROPINSI KALIMANTAN UTARA, INDONESIA - Mohammad Fathi Royyani; Oscar Efendy (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Ethnobotanical research on the utilization of plant species in Tau Lumbis village of North Kalimantan by Tagol and Akolod Dayaks ethnics has been conducted.Seventy seven species of plants have been recorded to be utilized by the people for various purposes from medicinal to magical-supranatural. Some literature reviews suggested that there was correlation of traditional knowledge and modern science in plant utilization by these ethnics.